Optimal design of proportional hazards based accelerated life testing plans. (29th October 2004) - Elsayed, E. A.; Jiao, Lixia
Accelerated life testing (ALT) is a widely used approach that estimates reliability of components or systems at normal operating conditions using data obtained at accelerated conditions. The accuracy of reliability estimates depends on the stress types, stress levels and corresponding sample sizes. In this paper, we present an efficient and practical approach for determining the appropriate stress levels and sample sizes of test units so as to obtain the most accurate reliability estimates at normal operating conditions. The optimal test plans are based on the proportional hazards model.